A multi-element composite admixture and a production process thereof
Patent Information
- Application Number
- CN202611037651.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-07-13
AI Technical Summary
[0004]本发明的目的在于提供一种多元复合掺合料及其生产工艺,解决了传统掺合料处理的混凝土脆性大易开裂的问题
[0015] The modified additive's side chains contain multiple carboxyl groups, which can strongly chelate with calcium ions from cement hydration products, achieving multi-point chemical anchoring. This firmly locks the hydrophobic chains onto the pore walls, preventing them from being washed away by water. Modified polyvinyl alcohol can form a three-dimensional support network in concrete, anchoring the matrix together and preventing cracks from forming in the concrete during hardening and early stress stages. Furthermore, the siloxanes in the molecular structure hydrolyze and connect with cement paste, while the long polysiloxane chains in the middle act as flexible ropes, freely extending in the pores to provide hydrophobicity and deformation capacity. At the same time, the hydroxyl groups in the molecule can form hydrogen bonds with oxygen atoms on the CSH gel, a cement hydration product, increasing the mechanical properties of the concrete.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of admixture preparation technology, specifically to a multi-component composite admixture and its production process. Background Technology
[0002] With the development of modern civil engineering towards super high-rise buildings, large-span structures, marine engineering, and harsh environments, increasingly higher requirements are being placed on the mechanical properties, durability, and workability of concrete. Traditional concrete is usually made by mixing cement, sand, aggregate, and water, and it inherently has defects such as high brittleness, low tensile strength, easy cracking, and strong hydrophilicity. To overcome these shortcomings, incorporating mineral admixtures and chemical additives into concrete mix design has become an indispensable technical means.
[0003] Currently, widely used mineral admixtures are mainly industrial by-products or natural minerals, such as fly ash, granulated blast furnace slag powder, silica fume, steel slag powder, and titanium slag. These materials improve the workability, increase later-stage strength and density of concrete, and reduce the heat of hydration through the "physical filling effect" and "volcanic ash effect," while also realizing the resource utilization of industrial solid waste. However, the incorporation of rigid admixtures such as silica fume and titanium slag, while increasing density, further increases the brittleness of concrete, leading to a decrease in its ultimate elongation and making it prone to cracking under drying shrinkage and temperature stress, thus affecting the performance of concrete. Summary of the Invention
[0004] The purpose of this invention is to provide a multi-component composite admixture and its production process, which solves the problem of brittle and easily cracked concrete treated with traditional admixtures.
[0005] The objective of this invention can be achieved through the following technical solutions: A production process for a multi-component composite admixture specifically includes the following steps: Step A1: Dissolve trimethylsilyl lithium in tetrahydrofuran, purge with nitrogen, stir and add tetramethylcyclotetrasiloxane at 200-300 r / min and 0℃, heat to 25-30℃ and react for 6-8 h, then add dimethylvinylchlorosilane and react for 1-1.5 h to obtain alkenyl polysiloxane; Step A2: Pentaerythritol tetrakis(3-mercaptopropionic acid) ester, alkenyl polysiloxane, 2,2-dimethoxy-2-phenylacetophenone and xylene are mixed and purged with nitrogen. The mixture is then reacted for 1-1.5 h under conditions of 150-200 r / min, 20-25℃ and 365 nm ultraviolet light irradiation to obtain branched polysiloxane. Step A3: Mix branched polysiloxane, acrylic acid, caster catalyst and xylene, purge with nitrogen, and react for 8-10 hours at a speed of 200-300 r / min and a temperature of 60-70℃ to obtain the modified additive. Step A4: Weigh the following raw materials by weight: 5-8 parts silica fume, 40-50 parts fly ash, 20-30 parts titanium slag, 1-3 parts modified additives and 1-2 parts modified polyvinyl alcohol. Mix the raw materials evenly to obtain a multi-component composite admixture.
[0006] Furthermore, the molar ratio of trimethylsilyllithium, tetramethylcyclotetrasiloxane and dimethylvinylchlorosilane in step A1 is 1:4:1.
[0007] Furthermore, the molar ratio of pentaerythritol tetrakis(3-mercaptopropionic acid) to alkenyl polysiloxane in step A2 is 1:4, and the amount of 2,2-dimethoxy-2-phenylacetophenone used is 1% of the mass of alkenyl polysiloxane.
[0008] Furthermore, the molar ratio of Si-H bonds on the branched polysiloxane to acrylic acid in step A3 is 1:1, and the amount of cassette catalyst used is 0.02% of the mass of acrylic acid.
[0009] Furthermore, the modified polyvinyl alcohol is prepared by the following steps: Step B1: Lithium dimethylvinylsilane is dissolved in tetrahydrofuran under nitrogen protection. The mixture is stirred at 200-300 r / min and 0°C, and hexamethylcyclotrisiloxane is added. The temperature is raised to 25-30°C, and the reaction proceeds for 6-8 hours. Then, dimethylchlorosilane is added, and the reaction proceeds for 1-1.5 hours to obtain a pretreated polysiloxane. The pretreated polysiloxane, mercaptopropyltrimethoxysilane, 2,2-dimethoxy-2-phenylacetophenone, and xylene are mixed and reacted under nitrogen protection at 150-200 r / min, 20-25°C, and 365 nm ultraviolet light irradiation for 1-1.5 hours to obtain a modified polysiloxane. Step B2: The modified polysiloxane, N-allyl tert-butyl carbamate, caster catalyst and xylene are mixed and purged with nitrogen. The mixture is reacted for 6-8 hours at a speed of 200-300 r / min and a temperature of 80-85℃ to obtain the functionalized polysiloxane. The functionalized polysiloxane is dissolved in xylene and stirred at a speed of 120-150 r / min and a temperature of 20-25℃. Trifluoroacetic acid is added and the mixture is reacted for 1-2 hours. The pH is then adjusted to 8 to obtain the amino polysiloxane. Step B3: Dissolve polyvinyl alcohol in dimethyl sulfoxide, stir and add saturated sodium hydroxide solution at a speed of 150-200 r / min and a temperature of 30-40℃, and react for 30-40 min. Then add epichlorohydrin and continue the reaction for 6-8 h to obtain epoxy polyvinyl alcohol. Dissolve epoxy polyvinyl alcohol in dimethyl sulfoxide, purge with nitrogen, stir and add amino polysiloxane at a speed of 120-150 r / min and a temperature of 30-40℃, and heat to 60-70℃ for 6-8 h to obtain modified polyvinyl alcohol.
[0010] Furthermore, in step B1, the molar ratio of lithium dimethylvinylsiloxane, hexamethylcyclotrisiloxane, and dimethylchlorosilane is 1:5:1, the molar ratio of pretreated polysiloxane and mercaptopropyltrimethoxysilane is 1:1, and the amount of 2,2-dimethoxy-2-phenylacetophenone used is 1.5% of the mass of mercaptopropyltrimethoxysilane.
[0011] Furthermore, in step B2, the molar ratio of the modified polysiloxane to N-allyl tert-butyl carbamate is 1:1, the amount of caster catalyst is 0.01% of the mass of N-allyl tert-butyl carbamate, and the ratio of functionalized polysiloxane to trifluoroacetic acid is 1:5.
[0012] Furthermore, in step B3, the ratio of polyvinyl alcohol, saturated sodium hydroxide solution, and epichlorohydrin is 10g:1mL:1.2mL, the polyvinyl alcohol is of type 1799, and the molar ratio of epoxy groups on the epoxy polyvinyl alcohol to amino polysiloxane is 1:1.
[0013] The beneficial effects of this invention are as follows: This invention discloses a multi-component composite admixture comprising the following raw materials: silica fume, fly ash, titanium slag, a modifier, and modified polyvinyl alcohol. The modifier uses trimethylsilyl alcohol lithium as an initiator and tetramethylcyclotetrasiloxane as a polymerization monomer to form a polysiloxane with a lithium silyl alcohol end and Si-H bonds on the side chain. Dimethylvinylchlorosilane is then added, causing the Si-Cl bonds on the dimethylvinylchlorosilane to react with the lithium silyl alcohol to obtain an alkenyl polysiloxane. Pentaerythritol tetrakis(3-mercaptopropionic acid) ester is reacted with the alkenyl polysiloxane, causing the thiol groups on the pentaerythritol tetrakis(3-mercaptopropionic acid) ester to react with the double bonds on the alkenyl polysiloxane to obtain a branched polysiloxane. The branched polysiloxane is reacted with acrylic acid, causing the Si-H bonds on the branched polysiloxane to react with the double bonds on the acrylic acid to obtain the modifier.
[0014] Modified polyvinyl alcohol (PVA) is produced using dimethylvinylsilyllithium as an initiator and hexamethylcyclotrisiloxane as a polymerization monomer to form a polysiloxane with a vinyl end and a lithium silanolate end. Dimethylchlorosilane is then added, causing the Si-Cl bonds on the dimethylchlorosilane to react with the lithium silanolate, yielding a pretreated polysiloxane. The pretreated polysiloxane is then reacted with mercaptopropyltrimethoxysilane, causing the double bonds on the pretreated polysiloxane to react with the mercapto groups on the mercaptopropyltrimethoxysilane, yielding a modified polysiloxane. Finally, the modified polysiloxane is reacted with N-... The reaction of tert-butyl allyl carbamate causes the Si-H bonds on the modified polysiloxane to react with the double bonds on N-tert-butyl allyl carbamate, thus preparing a functionalized polysiloxane. Trifluoroacetic acid is then used to prepare an aminopolysiloxane. Polyvinyl alcohol is then reacted with epichlorohydrin, causing some of the hydroxyl groups on the polyvinyl alcohol to react with the chlorine atom sites on the epichlorohydrin, thus preparing epoxy polyvinyl alcohol. Finally, epoxy polyvinyl alcohol is reacted with aminopolysiloxane to prepare modified polyvinyl alcohol.
[0015] The modified additive's side chains contain multiple carboxyl groups, which can strongly chelate with calcium ions from cement hydration products, achieving multi-point chemical anchoring. This firmly locks the hydrophobic chains onto the pore walls, preventing them from being washed away by water. Modified polyvinyl alcohol can form a three-dimensional support network in concrete, anchoring the matrix together and preventing cracks from forming in the concrete during hardening and early stress stages. Furthermore, the siloxanes in the molecular structure hydrolyze and connect with cement paste, while the long polysiloxane chains in the middle act as flexible ropes, freely extending in the pores to provide hydrophobicity and deformation capacity. At the same time, the hydroxyl groups in the molecule can form hydrogen bonds with oxygen atoms on the CSH gel, a cement hydration product, increasing the mechanical properties of the concrete. Detailed Implementation
[0016] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0017] Example 1: A production process for a multi-component composite admixture, specifically including the following steps: Step A1: Dissolve trimethylsilyl lithium in tetrahydrofuran, purge with nitrogen, stir and add tetramethylcyclotetrasiloxane at 200 r / min and 0 °C, heat to 25 °C and react for 6 h, then add dimethylvinylchlorosilane and react for 1 h to obtain alkenyl polysiloxane. Step A2: Pentaerythritol tetrakis(3-mercaptopropionic acid) ester, alkenyl polysiloxane, 2,2-dimethoxy-2-phenylacetophenone and xylene are mixed and purged with nitrogen. The mixture is then reacted for 1 hour at a rotation speed of 150 r / min, a temperature of 20 °C and irradiation with 365 nm ultraviolet light to obtain branched polysiloxane. Step A3: The branched polysiloxane, acrylic acid, caster catalyst and xylene are mixed, and nitrogen gas is introduced for protection. The mixture is reacted for 8 hours at a speed of 200 r / min and a temperature of 60℃ to obtain the modified additive. Step A4: Weigh the following raw materials by weight: 5 parts silica fume, 40 parts fly ash, 20 parts titanium slag, 1 part modified additive and 1 part modified polyvinyl alcohol. Mix the raw materials evenly to obtain a multi-component composite admixture.
[0018] The molar ratio of trimethylsilyllithium, tetramethylcyclotetrasiloxane and dimethylvinylchlorosilane in step A1 is 1:4:1.
[0019] The molar ratio of pentaerythritol tetrakis(3-mercaptopropionic acid) to alkenyl polysiloxane in step A2 is 1:4, and the amount of 2,2-dimethoxy-2-phenylacetophenone used is 1% of the mass of alkenyl polysiloxane.
[0020] The molar ratio of Si-H bonds on the branched polysiloxane to acrylic acid in step A3 is 1:1, and the amount of cassette catalyst used is 0.02% of the mass of acrylic acid.
[0021] The modified polyvinyl alcohol is prepared by the following steps: Step B1: Lithium dimethylvinylsilane was dissolved in tetrahydrofuran under nitrogen protection. The mixture was stirred at 200 r / min and 0°C, and hexamethylcyclotrisiloxane was added. The mixture was heated to 25°C and reacted for 6 hours. Then, dimethylchlorosilane was added and reacted for 1 hour to obtain a pretreated polysiloxane. The pretreated polysiloxane, mercaptopropyltrimethoxysilane, 2,2-dimethoxy-2-phenylacetophenone, and xylene were mixed and reacted under nitrogen protection at 150 r / min, 20°C, and 365 nm ultraviolet light irradiation for 1 hour to obtain a modified polysiloxane. Step B2: The modified polysiloxane, N-allyl tert-butyl carbamate, caster catalyst and xylene are mixed and purged with nitrogen. The mixture is reacted for 6 hours at a speed of 200 r / min and a temperature of 80 °C to obtain the functionalized polysiloxane. The functionalized polysiloxane is dissolved in xylene and stirred at a speed of 120 r / min and a temperature of 20 °C. Trifluoroacetic acid is added and the mixture is reacted for 1 hour. The pH is then adjusted to 8 to obtain the amino polysiloxane. Step B3: Dissolve polyvinyl alcohol in dimethyl sulfoxide, stir at 150 r / min and 30°C, add saturated sodium hydroxide solution, react for 30 min, add epichlorohydrin, and continue the reaction for 6 h to obtain epoxy polyvinyl alcohol. Dissolve epoxy polyvinyl alcohol in dimethyl sulfoxide, purge with nitrogen, stir at 120 r / min and 30°C, add amino polysiloxane, raise the temperature to 60°C, and react for 6 h to obtain modified polyvinyl alcohol.
[0022] In step B1, the molar ratio of lithium dimethylvinylsiloxane, hexamethylcyclotrisiloxane, and dimethylchlorosilane is 1:5:1, the molar ratio of pretreated polysiloxane and mercaptopropyltrimethoxysilane is 1:1, and the amount of 2,2-dimethoxy-2-phenylacetophenone used is 1.5% of the mass of mercaptopropyltrimethoxysilane.
[0023] The molar ratio of the modified polysiloxane and N-allyl tert-butyl carbamate in step B2 is 1:1, the amount of caster catalyst is 0.01% of the mass of N-allyl tert-butyl carbamate, and the ratio of functionalized polysiloxane to trifluoroacetic acid is 1:5.
[0024] The ratio of polyvinyl alcohol, saturated sodium hydroxide solution, and epichlorohydrin in step B3 is 10g:1mL:1.2mL. The polyvinyl alcohol is of type 1799, and the molar ratio of epoxy groups on the epoxy polyvinyl alcohol to amino polysiloxane is 1:1.
[0025] Example 2: A production process for a multi-component composite admixture, specifically including the following steps: Step A1: Dissolve trimethylsilyl lithium in tetrahydrofuran, purge with nitrogen, stir and add tetramethylcyclotetrasiloxane at 200 r / min and 0℃, heat to 30℃ and react for 7 h, then add dimethylvinylchlorosilane and react for 1.3 h to obtain alkenyl polysiloxane. Step A2: Pentaerythritol tetrakis(3-mercaptopropionic acid) ester, alkenyl polysiloxane, 2,2-dimethoxy-2-phenylacetophenone and xylene were mixed and purged with nitrogen. The mixture was reacted for 1.3 h at a rotation speed of 200 r / min, a temperature of 23 °C and irradiation with 365 nm ultraviolet light to obtain branched polysiloxane. Step A3: The branched polysiloxane, acrylic acid, caster catalyst and xylene are mixed, and nitrogen gas is introduced for protection. The mixture is reacted for 9 hours at a speed of 200 r / min and a temperature of 65℃ to obtain the modified additive. Step A4: Weigh the following raw materials by weight: 6 parts silica fume, 45 parts fly ash, 25 parts titanium slag, 2 parts modified additives and 1.5 parts modified polyvinyl alcohol. Mix the raw materials evenly to obtain a multi-component composite admixture.
[0026] The molar ratio of trimethylsilyllithium, tetramethylcyclotetrasiloxane and dimethylvinylchlorosilane in step A1 is 1:4:1.
[0027] The molar ratio of pentaerythritol tetrakis(3-mercaptopropionic acid) to alkenyl polysiloxane in step A2 is 1:4, and the amount of 2,2-dimethoxy-2-phenylacetophenone used is 1% of the mass of alkenyl polysiloxane.
[0028] The molar ratio of Si-H bonds on the branched polysiloxane to acrylic acid in step A3 is 1:1, and the amount of cassette catalyst used is 0.02% of the mass of acrylic acid.
[0029] The modified polyvinyl alcohol is prepared by the following steps: Step B1: Lithium dimethylvinylsilane was dissolved in tetrahydrofuran under nitrogen protection. The mixture was stirred at 200 r / min and 0°C, and hexamethylcyclotrisiloxane was added. The mixture was heated to 30°C and reacted for 7 h. Then, dimethylchlorosilane was added and reacted for 1.3 h to obtain pretreated polysiloxane. The pretreated polysiloxane, mercaptopropyltrimethoxysilane, 2,2-dimethoxy-2-phenylacetophenone, and xylene were mixed and reacted under nitrogen protection at 150 r / min, 25°C, and 365 nm ultraviolet light irradiation for 1.3 h to obtain modified polysiloxane. Step B2: The modified polysiloxane, N-allyl tert-butyl carbamate, caster catalyst and xylene are mixed and purged with nitrogen. The mixture is reacted for 7 hours at a speed of 300 r / min and a temperature of 83 °C to obtain the functionalized polysiloxane. The functionalized polysiloxane is dissolved in xylene and stirred at a speed of 120 r / min and a temperature of 25 °C. Trifluoroacetic acid is added and the mixture is reacted for 1.5 hours. The pH is then adjusted to 8 to obtain the amino polysiloxane. Step B3: Dissolve polyvinyl alcohol in dimethyl sulfoxide, stir at 200 r / min and 35°C, add saturated sodium hydroxide solution, react for 35 min, add epichlorohydrin, and continue the reaction for 7 h to obtain epoxy polyvinyl alcohol. Dissolve epoxy polyvinyl alcohol in dimethyl sulfoxide, purge with nitrogen, stir at 150 r / min and 35°C, add amino polysiloxane, raise the temperature to 65°C, and react for 7 h to obtain modified polyvinyl alcohol.
[0030] In step B1, the molar ratio of lithium dimethylvinylsiloxane, hexamethylcyclotrisiloxane, and dimethylchlorosilane is 1:5:1, the molar ratio of pretreated polysiloxane and mercaptopropyltrimethoxysilane is 1:1, and the amount of 2,2-dimethoxy-2-phenylacetophenone used is 1.5% of the mass of mercaptopropyltrimethoxysilane.
[0031] The molar ratio of the modified polysiloxane and N-allyl tert-butyl carbamate in step B2 is 1:1, the amount of caster catalyst is 0.01% of the mass of N-allyl tert-butyl carbamate, and the ratio of functionalized polysiloxane to trifluoroacetic acid is 1:5.
[0032] The ratio of polyvinyl alcohol, saturated sodium hydroxide solution, and epichlorohydrin in step B3 is 10g:1mL:1.2mL. The polyvinyl alcohol is of type 1799, and the molar ratio of epoxy groups on the epoxy polyvinyl alcohol to amino polysiloxane is 1:1.
[0033] Example 3: A production process for a multi-component composite admixture, specifically including the following steps: Step A1: Dissolve trimethylsilyl lithium in tetrahydrofuran, purge with nitrogen, stir and add tetramethylcyclotetrasiloxane at 300 r / min and 0℃, heat to 30℃ and react for 8 h, then add dimethylvinylchlorosilane and react for 1.5 h to obtain alkenyl polysiloxane. Step A2: Pentaerythritol tetrakis(3-mercaptopropionic acid) ester, alkenyl polysiloxane, 2,2-dimethoxy-2-phenylacetophenone and xylene are mixed and purged with nitrogen. The mixture is then reacted for 1.5 h at a rotation speed of 200 r / min, a temperature of 25 °C and irradiation with 365 nm ultraviolet light to obtain branched polysiloxane. Step A3: The branched polysiloxane, acrylic acid, caster catalyst and xylene are mixed, and nitrogen gas is introduced for protection. The mixture is reacted for 10 hours at a speed of 300 r / min and a temperature of 70℃ to obtain the modified additive. Step A4: Weigh the following raw materials by weight: 8 parts silica fume, 50 parts fly ash, 30 parts titanium slag, 3 parts modified additives and 2 parts modified polyvinyl alcohol. Mix the raw materials evenly to obtain a multi-component composite admixture.
[0034] The molar ratio of trimethylsilyllithium, tetramethylcyclotetrasiloxane and dimethylvinylchlorosilane in step A1 is 1:4:1.
[0035] The molar ratio of pentaerythritol tetrakis(3-mercaptopropionic acid) to alkenyl polysiloxane in step A2 is 1:4, and the amount of 2,2-dimethoxy-2-phenylacetophenone used is 1% of the mass of alkenyl polysiloxane.
[0036] The molar ratio of Si-H bonds on the branched polysiloxane to acrylic acid in step A3 is 1:1, and the amount of cassette catalyst used is 0.02% of the mass of acrylic acid.
[0037] The modified polyvinyl alcohol is prepared by the following steps: Step B1: Lithium dimethylvinylsilane was dissolved in tetrahydrofuran under nitrogen protection. The mixture was stirred at 300 r / min and 0°C, and hexamethylcyclotrisiloxane was added. The mixture was heated to 30°C and reacted for 8 hours. Then, dimethylchlorosilane was added and reacted for 1.5 hours to obtain pretreated polysiloxane. The pretreated polysiloxane, mercaptopropyltrimethoxysilane, 2,2-dimethoxy-2-phenylacetophenone, and xylene were mixed and reacted under nitrogen protection at 200 r / min, 25°C, and 365 nm ultraviolet light irradiation for 1.5 hours to obtain modified polysiloxane. Step B2: The modified polysiloxane, N-allyl tert-butyl carbamate, caster catalyst and xylene are mixed and purged with nitrogen. The mixture is reacted for 8 hours at a speed of 300 r / min and a temperature of 85 °C to obtain the functionalized polysiloxane. The functionalized polysiloxane is dissolved in xylene and stirred at a speed of 150 r / min and a temperature of 25 °C. Trifluoroacetic acid is added and the mixture is reacted for 2 hours. The pH is then adjusted to 8 to obtain the amino polysiloxane. Step B3: Dissolve polyvinyl alcohol in dimethyl sulfoxide, stir at 200 r / min and 40°C, add saturated sodium hydroxide solution, react for 40 min, add epichlorohydrin, and continue the reaction for 8 h to obtain epoxy polyvinyl alcohol. Dissolve epoxy polyvinyl alcohol in dimethyl sulfoxide, purge with nitrogen, stir at 150 r / min and 40°C, add amino polysiloxane, raise the temperature to 70°C, and react for 8 h to obtain modified polyvinyl alcohol.
[0038] In step B1, the molar ratio of lithium dimethylvinylsiloxane, hexamethylcyclotrisiloxane, and dimethylchlorosilane is 1:5:1, the molar ratio of pretreated polysiloxane and mercaptopropyltrimethoxysilane is 1:1, and the amount of 2,2-dimethoxy-2-phenylacetophenone used is 1.5% of the mass of mercaptopropyltrimethoxysilane.
[0039] The molar ratio of the modified polysiloxane and N-allyl tert-butyl carbamate in step B2 is 1:1, the amount of caster catalyst is 0.01% of the mass of N-allyl tert-butyl carbamate, and the ratio of functionalized polysiloxane to trifluoroacetic acid is 1:5.
[0040] The ratio of polyvinyl alcohol, saturated sodium hydroxide solution, and epichlorohydrin in step B3 is 10g:1mL:1.2mL. The polyvinyl alcohol is of type 1799, and the molar ratio of epoxy groups on the epoxy polyvinyl alcohol to amino polysiloxane is 1:1.
[0041] Comparative Example 1: In this comparative example, ethylene dithiol was used instead of pentaerythritol tetrakis(3-mercaptopropionic acid) ester, while the other steps were the same as in Example 1.
[0042] Comparative Example 2: Compared with Example 1, this comparative example uses lithium trimethylsilanolate dissolved in tetrahydrofuran, under nitrogen protection, stirred and added hexamethylcyclotrisiloxane at a speed of 200 r / min and a temperature of 0°C, heated to 25°C and reacted for 6 h, then added dimethylchlorosilane and reacted for 1 h. The product obtained replaces the modified polysiloxane, and the remaining steps are the same.
[0043] Comparative Example 3: This comparative example uses polyvinyl alcohol instead of modified polyvinyl alcohol, while the other steps are the same as in Example 1.
[0044] The admixtures obtained in Examples 1-3 and Comparative Examples 1-3 were added to 360 parts of cement (PO 42.5), 780 parts of medium sand, 1080 parts of 5mm crushed stone, and 180 parts of water to prepare concrete. According to the standard GB / T50081-2019, 100mm×100mm×100mm specimens were prepared, and the compressive strength and flexural strength were tested after 28 days of curing. According to the standard GB / T50082-2024, 100mm×100mm×515mm specimens were prepared, the initial length was measured after 3 days of curing, and the shrinkage rate was calculated after another 28 days of curing. The test results are shown in Table 1 below.
[0045] Table 1
[0046] As shown in Table 1, this application has excellent mechanical properties and anti-shrinkage effect.
[0047] The above description is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the concept of the invention or exceed the scope defined in the claims, they should all fall within the protection scope of the present invention.
Claims
1. A production process for a multi-component composite admixture, characterized in that: Specifically, the steps include the following: Step A1: Dissolve trimethylsilyl lithium in tetrahydrofuran, purge with nitrogen for protection, stir and add tetramethylcyclotetrasiloxane, heat and react, then add dimethylvinylchlorosilane to react and obtain alkenyl polysiloxane. Step A2: Pentaerythritol tetrakis(3-mercaptopropionic acid) ester, alkenyl polysiloxane, 2,2-dimethoxy-2-phenylacetophenone and xylene are mixed, and the mixture is purged with nitrogen gas and reacted under ultraviolet light to obtain branched polysiloxane. Step A3: Mix branched polysiloxane, acrylic acid, caster catalyst and xylene, purge with nitrogen gas and react to obtain modified additive. Step A4: Weigh the following raw materials by weight: 5-8 parts silica fume, 40-50 parts fly ash, 20-30 parts titanium slag, 1-3 parts modified additives and 1-2 parts modified polyvinyl alcohol. Mix the raw materials evenly to obtain a multi-component composite admixture. The modified polyvinyl alcohol is prepared by the following steps: Step B1: Lithium dimethylvinylsilane is dissolved in tetrahydrofuran, protected by nitrogen gas, stirred and hexamethylcyclotrisiloxane is added, heated and reacted, and then dimethylchlorosilane is added to carry out the reaction to obtain pretreated polysiloxane. The pretreated polysiloxane, mercaptopropyltrimethoxysilane, 2,2-dimethoxy-2-phenylacetophenone and xylene are mixed, protected by nitrogen gas, and reacted by ultraviolet light to obtain modified polysiloxane. Step B2: Mix the modified polysiloxane, N-allyl tert-butyl carbamate, caster catalyst and xylene, purge with nitrogen and react to obtain functionalized polysiloxane. Dissolve the functionalized polysiloxane in xylene, stir and add trifluoroacetic acid, react and adjust the pH to alkaline to obtain amino polysiloxane. Step B3: Dissolve polyvinyl alcohol in dimethyl sulfoxide, stir and add saturated sodium hydroxide solution, react, then add epichlorohydrin and continue the reaction to obtain epoxy polyvinyl alcohol. Dissolve epoxy polyvinyl alcohol in dimethyl sulfoxide, purge with nitrogen for protection, stir and add amino polysiloxane, heat and react to obtain modified polyvinyl alcohol.
2. The production process of the multi-component composite admixture according to claim 1, characterized in that: The molar ratio of trimethylsilyllithium, tetramethylcyclotetrasiloxane and dimethylvinylchlorosilane in step A1 is 1:4:
1.
3. The production process of the multi-component composite admixture according to claim 1, characterized in that: The molar ratio of pentaerythritol tetrakis(3-mercaptopropionic acid) ester and alkenyl polysiloxane in step A2 is 1:
4.
4. The production process of the multi-component composite admixture according to claim 1, characterized in that: The molar ratio of Si-H bonds on the branched polysiloxane and acrylic acid in step A3 is 1:
1.
5. The production process of the multi-component composite admixture according to claim 1, characterized in that: The molar ratio of lithium dimethylvinylsiloxane, hexamethylcyclotrisiloxane and dimethylchlorosilane in step B1 is 1:5:1, and the molar ratio of pretreated polysiloxane and mercaptopropyltrimethoxysilane is 1:
1.
6. The production process of the multi-component composite admixture according to claim 1, characterized in that: The molar ratio of the modified polysiloxane and N-allyl tert-butyl carbamate mentioned in step B2 is 1:1, and the ratio of the functionalized polysiloxane to trifluoroacetic acid is 1:
5.
7. The production process of the multi-component composite admixture according to claim 1, characterized in that: The ratio of polyvinyl alcohol, saturated sodium hydroxide solution, and epichlorohydrin in step B3 is 10g:1mL:1.2mL, and the molar ratio of epoxy groups on the epoxy polyvinyl alcohol to amino polysiloxane is 1:
1.
8. A multi-component composite admixture, characterized in that: Prepared according to any one of the preparation methods described in claims 1-7.
Citation Information
Patent Citations
Preparation method of high-stability solvent composite membrane
CN118047968A
High-light-transmittance heat-insulation ionic intermediate film and preparation process thereof
CN122213877A